Concentration in international markets: Evidence from US imports - Alessandra Bonfiglioli; Rosario Crinò; Gino Alessandro Gancia (Queen Mary University of London, School of Economics and Finance, 2019)
We use transaction-level data to study changes in the concentration of US imports. Concentration has fallen in the typical industry, while it is stable by industry and country of origin. The fall in concentration is driven by the extensive margin: the number of exporting firm has grown, and the number of exported products has fallen more for top firms. Instead, average revenue per product of top firms has increased. At the industry level, top firms are converging, but top firms within country are diverging. These facts suggest that intensi.ed competition in international markets coexists with growing concentration among national producers.
Keywords: E23; F12; F14; L11; R12; 330; Superstar Firms; Concentration; US Imports; Firm Heterogeneity; International Trade